Workshop Kekayaan Intelektual sebagai Upaya Peningkatan Pemahaman dalam Rangka Pengenalan dan Perlindungan Indikasi Geografis Minyak Kayu Putih Namlea Pulau Buru - Muchtar Anshary Hamid Labetubun; Rory Jeff Akyuwen; Theresia Nolda Agnes Narwadan (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Indonesia is a country that has many natural resources that have the potential to be related to Geographical Indications, one of which is Putiah Wood Oil originating from Buru Island.Purposes of Devotion: To provide efforts to increase understanding in the context of the introduction and protection of Geographical Indications of Eucalyptus Oil on Buru Island. Method of Devotion: The method used in this activity is in the form of a workshop for the Office of Cooperatives, the Department of Tourism, the Department of Industry and Trade, the Department of Fisheries, the Department of Agriculture and Micro, Small and Medium Enterprises in Namlea, Buru Regency through material presentation and questions and answers.Results of the Devotion: Eucalyptus Oil until now has not Registered as a Geographical Indication product. If this is allowed, it is possible that at one time there could be disputes related to unilateral claims or public deception. Eucalyptus Oil on Buru Island has the potential to be protected as a Geographical Indication and provides legal certainty for Eucalyptus Oil if registration is the main requirement for Wood Oil to obtain legal protection.